Gene expression reveals evidence for EGFR‐dependent proximal‐distal limb patterning in a myriapod. Issue 3 (26th April 2017) - Janssen, Ralf
Abstract : Evolution of segmented limbs is one of the key innovations of Arthropoda, allowing development of functionally specific specialized head and trunk appendages, a major factor behind their unmatched evolutionary success. Proximodistal limb patterning is controlled by two regulatory networks in the vinegar fly Drosophila melanogaster, and other insects. The first is represented by the function of the morphogens Wingless (Wg) and Decapentaplegic (Dpp); the second by the EGFR‐signaling cascade. While the role of Wg and Dpp has been studied in a wide range of arthropods representing all main branches, that is, Pancrustacea (= Hexapoda + Crustacea), Myriapoda and Chelicerata, investigation of the potential role of EGFR‐signaling is restricted to insects (Hexapoda). Gene expression analysis of Egfr, its potential ligands, and putative downstream factors in the pill millipede Glomeris marginata (Myriapoda: Diplopoda), reveals that—in at least mandibulate arthropods—EGFR‐signaling is likely a conserved regulatory mechanism in proximodistal limb patterning.